If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2y + 7) = 21.5 Reorder the terms: 6(7 + 2y) = 21.5 (7 * 6 + 2y * 6) = 21.5 (42 + 12y) = 21.5 Solving 42 + 12y = 21.5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 12y = 21.5 + -42 Combine like terms: 42 + -42 = 0 0 + 12y = 21.5 + -42 12y = 21.5 + -42 Combine like terms: 21.5 + -42 = -20.5 12y = -20.5 Divide each side by '12'. y = -1.708333333 Simplifying y = -1.708333333
| 2g-3=345 | | 72x+49=101 | | 40.4496-8y=121.5 | | -5=n/3=8 | | -5-3-4-1= | | 3k-3k+3k-2k=20 | | 3y+23= | | 3xyz+2x=w | | 12+-(7-3t)=-8+-30 | | 5a+3+3a=27 | | -7+6+9= | | 21x+24=69 | | -8+8+1= | | X+y+5y= | | 4+13-21= | | 4x+10=6x+12 | | logbN=x | | 8m=10m+6 | | 2-5X=3-9X | | Y=x+3+2x-5+x+7 | | 0.6/9.8=x/4.8 | | -9(x+8)=9+10x | | X=0.32/8 | | 5s^2+2s-7=0 | | y=3x^2+8 | | 6x-18/4=7x | | Y=4x+2+7x+7+5x+4 | | 9x-7/8=14x | | y=6(-3)+25 | | 2x^3+y^3=20 | | 5x+2(6x+25)=-1 | | log(4x-2)=1 |